Kurkumin sebagai Agen Penghambat Penurunan Bobot Badan dan Skleroderma pada Mencit Akibat Induksi Bleomisin - Rahmi, Annisa; Baharun, Abdullah; Juniantito, Vetnizah; Setyono, Agus (JURNAL KAJIAN VETERINER, 2024)
Curcumin is the main active ingredient from turmeric plant (Curcuma longa) has been known as anti-oxidant and anti-inflammatory agent. Bleomycin is an anti-cancer drug which have side effects such as scleroderma and body weight loss in animals or human. This study was aimed to determined biological effects of curcumin to bleomycin-induced scleroderma and body weight loss in mice (Mus musculus). Sixteen male mice (ddy strain) were devided in to four groups: (i) negative control, received aquadest injection 0,1 ml (SC); (ii) bleomycin (BLM), received 0,1 ml bleomycin 1 mg/ml SC injection; (iii) curcumin (CMN), received aquadest injection 0,1 ml (SC) and 100 mg/kg BW curcumin in 0,5% carboxymethylcellulose (IP); and (iv) BLM+ CMN, received 0,1 ml bleomycin 1 mg/ml SC injection and 100 mg/kg BW curcumin in 0,5% carboxymethylcellulose (IP). All treatments are given every day for 4 weeks and body weigh were measured every week. The dorsal skin as injection’s dot evaluated by histopathology assessment with HE stains. BLM group showed body weight and hair follicles were loss significantly with skin fibrosis and inflammatory cells infiltration. However, CMN treatment showed opposite results in BLM-treated mice. Conclusively, this study showed CMN treatment may inhibit skin fibrogenesis in BLM-induced scleroderma and body weight loss.